Ecofeminism and Cultural-Value System in Traditional Paddy Farming: A Folklore from West Borneo - Agung, Antonius Setyawan Sugeng Nur; Surtikanti, Monika Widyastuti; Wedhowerti, Wedhowerti (Soegijapranata Catholic University, 2024)
Ne’ Balungkur represents the inherited living value of traditional paddy farming lived by Dayak Kanayatn. Concerning the ecofeminism ideology, this study aims to reveal the existence of women and nature in traditional paddy farming in Ne’ Balungkur folklore in relation to the cultural-value system. Enriching the ecofeminism perspective in this study, the community prominent figure of the Dayak Kanayatn community was interviewed to give triangular validity to the data interpretation. Exhibiting comprehensive ecofeminism analysis to show the representation of woman empowerment through Dayak Kanayatn's code of conduct in planting to harvesting paddy is the main contribution of this study. Ne’ Balungkur demonstrates how women of the Dayak Kanayatn tribe are respected for their roles in traditional paddy farming and cultivation. This woman’s role in Ne’ Balungkur folklore challenges the customary male supremacy in Indonesian agriculture. This study is also able to identify the pattern of the cultural-value system. The pattern of the domain, taxonomy, componential, and cultural theme analysis shows that the current religious system, which blends ritual, custom, and religion into a single thought, has always been entwined with culture and education. Numerous opportunities for incorporating local folklore especially from West Borneo into official educational contexts are suggested by this study